Cytokine dysregulation in oral lichen planus: Differential expression of IFN-γ and IL-4 in erosive and non-erosive subtypes - Xiang Zhao; Yan Du; Huabing Ge (European Journal of Inflammation)
Introduction: Oral lichen planus (OLP) is a chronic inflammatory disease with immune system dysregulation playing a key role in its pathogenesis. Cytokines such as IFN-γ and IL-4 are critical in modulating the Th1/Th2 balance, which is implicated in the disease’s progression. This study aimed to evaluate the expression of IFN-γ and IL-4 in the peripheral blood of OLP patients and explore differences between erosive and non-erosive subtypes. Materials and Methods: A retrospective analysis included 58 OLP patients (30 non-erosive and 28 erosive) and 58 healthy controls enrolled from June 2020 to June 2022. mRNA levels of IFN-γ and IL-4 were quantified using RT-PCR, while protein expression was determined via ELISA. Results: OLP patients demonstrated significantly elevated IFN-γ and IL-4 mRNA and protein levels compared to healthy controls ( p < .05). Both erosive and non-erosive subtypes showed increased cytokine expression ( p < .05). IL-4 levels were higher in the erosive subtype ( p < .05), while IFN-γ levels showed no significant difference between subtypes ( p > .05). The IFN-γ/IL-4 ratio was significantly higher in OLP patients than in controls ( p < .05), but lower in the erosive subtype compared to the non-erosive group ( p < .05). Conclusion: Elevated IFN-γ and IL-4 expression, particularly the skewed IFN-γ/IL-4 ratio in erosive OLP, highlights the importance of Th1/Th2 imbalance in OLP pathogenesis. This warrants further investigation into cytokine-targeted therapies for this chronic condition.